PENINGKATAN MINAT DAN PRESTASI BELAJAR AL- QUR’AN DENGAN METODE DAN BAHAN AJAR IQRO’ BRAILLE PADA SISWA KELAS III SDLB–A YEKETUNIS YOGYAKARTA - Hindatulatifah Hindatulatifah (Jurnal Pendidikan Agama Islam, 2017)
The success rate of reading the Qur'an for students with visual impairment depends on the level of sensitivity of students. Braille Qur'an learning method that is applied so far is qowa'idulimla' (dictation) that emphasizes writing skills but less able to explore the ability to read. To overcome these problems need appropriate learning strategies and media and teaching materials in form of Arabic Braille writing. This research is a classroom action research by taking the form of collaborative research conducted in two cycles. Subjects in this study were students of grade III SDLB-A Yaketunis. Results showed that application of teaching materials iqro 'Braille can increase students' learning interest in learning the Braille Qur'an. Pre action results that show 68.75% (medium category), in the first cycle increased to 87.08% (high category), and in cycle II increased again to 90% (high category). Implementation of teaching materials Iqro 'Braille also improve Achievement of Learning PAI. This is seen from scores of learning achievement on pre-action and post action.